When Mom Has Migraine: An Observational Study of the Impact of Parental Migraine on Adolescent Children. Issue 2 (31st October 2018) - Seng, Elizabeth K.; Mauser, Emily D.; Marzouk, Maya; Patel, Zarine S.; Rosen, Noah; Buse, Dawn C.
Abstract : Objective: The current study aimed to describe the impact of parental migraine on adolescent children (aged 11–17) living at home with a parent with migraine. Background: Emerging evidence suggests that migraine impacts the family members of people with migraine. However, there has been little research to evaluate the perspective of the child of a parent with migraine. Methods: This cross‐sectional observational study included parents who met International Classification of Headache Disorders criteria for migraine and their 11–17‐year‐old children currently living with the parent with migraine recruited from neurologist offices and online. Parents completed measures of demographics, a diagnostic migraine criteria screener, parental illness impact (Parental Illness Impact Survey – Revised; subscales = Burden of Daily Help, Emotional Impact, Social Impact, Communication and Understanding, Impact on Personal Future, Friends Reactions, Parent/Child Relationship, and Global Well‐Being), migraine‐related disability (MIDAS), headache attack frequency, and headache attack pain intensity. Children completed measures of demographics, parental illness impact, and a migraine diagnostic screener if applicable. Results: Children (n = 40) reported the greatest impact of their parent's migraine on the Global Well‐Being (M = 3.3, SD = 0.9) and Parent/Child Relationship (M = 3.5, SD = 0.6) subscales. There were no significant differences between the average child and parent rating of parental migraine impact on children. Correlations between parent and child ratings of parental migraine impact were strongest for the Social Impact subscale ( ρ = 0.55, P < .001), and non‐significant for the Parent/Child Relationship ( ρ = 0.13, P = .416) and Friends Reactions ( ρ = 0.18, P = .257) subscales. Higher attack frequency and endorsing severe disability on the MIDAS were associated with higher child‐rated impact (eg, lower scores) on Global Well‐Being (frequency ρ = −0.35, P = .028; MIDAS t (38) = 2.74, P = .009) and Impact on Personal Future (frequency ρ = −0.41, P = .009; MIDAS t (35.7) = 2.49, P = .017) subscales. Higher attack pain intensity was associated with higher child‐rated impact (eg, lower scores) on Burden of Daily Help ( r = −0.34, P = .031) and Emotional Impact ( r = −0.40, P = .010). Over half of children (23/40, 57.5%) reported some kind of service or intervention to help them manage the impact of their parent's migraine on their lives would be helpful. Conclusions: Parental migraine impacts children aged 11–17 living in the home, particularly in the domains of global well‐being and the parent/child relationship. Parent and child reports are not strongly correlated across all domains of parental impact.